2020
DOI: 10.1016/j.nmni.2020.100753
|View full text |Cite
|
Sign up to set email alerts
|

Baseline electrolyte abnormalities would be related to poor prognosis in hospitalized coronavirus disease 2019 patients

Abstract: Electrolyte abnormalities are not uncommon in coronavirus disease 2019 (COVID-19). Several studies have suggested that various electrolyte imbalances seem to have an impact on disease prognosis. However, no study has primarily focused on the effect of baseline electrolyte abnormalities on disease outcome. In this study, we assessed the validity of the hypothesis that baseline electrolyte imbalances may be related to unfavourable outcomes in hospitalized COVID-19 patients. Design of the study was retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
117
5
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(137 citation statements)
references
References 27 publications
11
117
5
4
Order By: Relevance
“…This electrolyte imbalance will in turn affect the different body organ system function that could compromise the body's appropriate response to the stress caused by the disease thereby leading to more severe disease, complication and death. This is also demonstrated in other studies, where both increased and decreased levels of Na and K are found to be associated with severe disease states [19][20][21].…”
Section: Plos Onesupporting
confidence: 83%
See 1 more Smart Citation
“…This electrolyte imbalance will in turn affect the different body organ system function that could compromise the body's appropriate response to the stress caused by the disease thereby leading to more severe disease, complication and death. This is also demonstrated in other studies, where both increased and decreased levels of Na and K are found to be associated with severe disease states [19][20][21].…”
Section: Plos Onesupporting
confidence: 83%
“…Electrolyte imbalance in both directions, hypo-and hyper-levels were reported for sodium, potassium and calcium levels among patients with severe disease and worse outcome, hypothesized to result from the effect of the disease on the body system or the medication side effects [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…32 Some studies have shown that the majority of COVID-19 cases have electrolyte abnormalities correlated with a high risk of intensive care needs, mechanical ventilation and encephalopathy events with high mortality rates and longer treatment days. 33,34 Comparable to some other studies, most cases found that most cases had hyponatremia (55.6%). Tezcan, et al mentions that hyponatremia is the most common electrolyte abnormality compared to other electrolyte abnormalities.…”
Section: Discussionsupporting
confidence: 57%
“…In addition, hyponatremia can also be used as an independent predictor of poor prognosis in COVID-19 patients. 34 One of the clinical picture in COVID-19 is the development of lung injuries that have the potential to cause ARDS. Pneumonia and ARDS usually develop late in the course of infection between 5-10 days from the onset of clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…There are 2032 patients from 7 studies included in this systematic review and meta-analysis [ [12] , [13] , [14] , [15] , [16] , [17] , [18] ] ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%